INDONESIA’S “MARITIME WORLD FULCRUM” AND CHINA’S “MARITIME SILK ROAD” - L. M. Efimova (Vestnik MGIMO-Universiteta)
In 2014 the newly elected Indonesian president Joko Widodo declared his doctrine “In- donesia – World Maritime Fulcrum”. His intention is to transform Indonesia which connects two great oceans – Indian and Pacific – into a strategic logistic and trade world hub as well as the main supplier of sea products for the world market. Indonesian government plans to build 35 deepwater and ordinary ports across the archipelago during the next five years. The implementation of the project demands colossal money investments and gigantic volumes of work. Indonesia cannot do it alone, the country needs foreign investors and constructors. A number of Asian and Europe countries expressed their intentions to cooperate with Indonesia in the maritime sector. But the most interested turned out to be China which expressed its ardent desire to cooperate with Indonesia in the sector of maritime industry. And it is quite understandable taking into consideration that China worked out its own project “Maritime Silk Road” which comprises the same sea territory as Indonesia’s “Maritime Fulcrum” project. Chinese leaders invited Indonesia to closely cooperate in implementing these two projects which are mutually coinciding and complementary. Indonesian leaders gladly accepted this invitation hoping to gain a lot from cooperation with China. Chinese “Maritime Silk Road” project will contribute to the development of inter-island communicativity which is strongly needed especially in the eastern part of Indonesian archipelago. In addition China agreed to participate in building and reconstructing Indonesian ports. Some Indonesian observers greet close cooperation with China as a very profitable business opportunity but others express apprehensions that too close cooperation with China could be dangerous for Indonesian sovereignty over its territorial waters.